A Peculiar Interpretation of the Constitutional Principle of "One Person, One Vote" in Poland: Voter (In)equality in the Elections to 1, 200 Local Legislatures. (November 2017) - Pierzgalski, Michał; Stępień, Paweł
The adoption of new redistricting plans for the 2014 elections to local legislatures in Poland resulted in significant violations of the "one person, one vote" principle. This article shows the results of the first comparative study measuring within-country variation of voter inequality, using data from the 2014 Polish local elections to 1, 200 commune or municipal councils, that is, local legislatures. Voter inequality is usually examined at the country or state level, while studies that take into account within-country variation of malapportionment, using local election data, are neglected by scholars. To put our research in a broader context, we compared levels of malapportionment in Poland with internationally recognized standards (contained, e.g., in the Code of Good Practice in Electoral Matters issued by the Venice Commission) as to the acceptable levels of deviations from the "ideal" population, and also with empirical findings on the levels of voter inequality in other countries. We argue that the significant vote–value disparities in elections to commune councils in Poland result primarily from the disadvantages of the Polish 2011 Election Code. When it comes to local legislature elections in the vast majority of communes that are not the so-called county-status towns, the legally permitted deviation from the ideal district population ranges from +50 percent to −50 percent. Even considering the standards of redistricting for local elections, the interpretation of the "one person, one vote" principle is rather peculiar in Polish commune elections.